Non-valued Changeover Time Measures for Hiddxen Time Loss in Automotive Mechanical Component Production - H, Abdul Rasib A. .; F, Mohamad Rafaai Z. . (International Journal of Engineering and Technology, 2018)
Â Generally, Hidden Time Loss exists besides all procedures and thus it has the direct influence on the rate of productivity. In the line of production, the most prominent tool to measure the performance is Overall Equipment Efficiency. Availability of equipment is one of the component to measure Overall Equipment Efficiency to cater the Hidden Time Loss. Though, in manual assembly and semi-automatic assembly procedure, the Overall Equipment Efficiency is not good fit to measure operational performance of assembly procedure. Along the manual assembly and semi-automatic assembly procedures some Hidden Time Loss has occurred particularly when same line of production provides high variety of product. Therefore, the current research introduces the Non-valued Changeover Time as one component of Time Loss Measures in assemble produces. A comprehensive literature analysis is done on the production operations along with the measures of performance to develop the Non-valued Change-over Time structure. Basically, a case study of two companies of automotive manufacturing is used to find the validity of structure of Non-valued Change-over Time. It is concluded that Non-valued Change-over Time is one of the measure of Hidden Time Loss in manual as well as semi-automatic assembly procedures.